The Sebaceous Gland: A Key Player in the Balance Between Homeostasis and Inflammatory Skin Diseases - Sarah Mosca; Monica Ottaviani; Stefania Briganti; Anna Di Nardo; Enrica Flori (Cells)
The sebaceous gland (SG) is an integral part of the pilosebaceous unit and is a very active and dynamic organ that contributes significantly to the maintenance of skin homeostasis. In addition to its primary role in sebum production, the SG is involved in the maintenance of skin barrier function, local endocrine/neuroendocrine function, the innate immune response, and the regulation of skin bacterial colonization. Structural and functional alterations of SGs leading to the dysregulation of sebum production/composition and immune response may contribute to the pathogenesis of inflammatory dermatoses. This review summarises the current knowledge on the contribution of SGs to the pathogenesis of common inflammatory skin diseases. These findings are crucial for the development of more effective therapeutic strategies for the treatment of inflammatory dermatoses.